2016
DOI: 10.1177/1474704916681300
|View full text |Cite
|
Sign up to set email alerts
|

Female Cigarette and Alcohol Consumption as a Short-Term Mating Strategy

Abstract: In developed countries, the traditional gender gap in youth smoking and drinking is closing. As tobacco and alcohol are more harmful to women than to men, this is an alarming trend. As men are generally more short-term oriented in their sexuality than women, and given that cigarette and alcohol use are still considered masculine behaviors, we explored if female smoking and drinking can function as a short-term mating strategy. By means of a between-subjects experiment (N ¼ 218), men's perceptions of female smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 83 publications
3
26
1
5
Order By: Relevance
“…Based on the above research, recent studies suggest that risky drinking behavior could function as a short-term mating strategy for young adults (Vincke, 2016a(Vincke, , 2016b. Accordingly, in actual mating situations, young adults following a short-term mating strategy might drink high amounts of alcohol as a signal to the opposite sex.…”
Section: Alcohol Use As Courtship Behaviormentioning
confidence: 99%
“…Based on the above research, recent studies suggest that risky drinking behavior could function as a short-term mating strategy for young adults (Vincke, 2016a(Vincke, , 2016b. Accordingly, in actual mating situations, young adults following a short-term mating strategy might drink high amounts of alcohol as a signal to the opposite sex.…”
Section: Alcohol Use As Courtship Behaviormentioning
confidence: 99%
“…Their powerful position may encourage classmates to follow their lead, a process that was investigated by Ali, Amialchuk and Nikaj (2014). They showed that an increase in alcohol use made adolescents more popular, and a recent study suggested that female adolescents are more sexually attracted to smoking and drinking boys as short-term mates (Vincke, 2016). Smoking appeared more present among populistic late adolescents than either social-popular or unpopular classmates.…”
Section: Routes To Consensual Popularity and Behaviorsmentioning
confidence: 99%
“…Smoking appeared more present among populistic late adolescents than either social-popular or unpopular classmates. Vincke (2016) showed that boys who smoked were perceived by girls more as pursuers of a short-term mating than a long-term mating strategy. Smoking and drinking males were viewed as more attractive.…”
Section: Routes To Consensual Popularity and Behaviorsmentioning
confidence: 99%
“…In a socio‐ecological view, by frequenting bars, parties and other places that promote alcohol consumption, adolescents and young adults are also exposed to tobacco marketing, peer smoking and role‐modelling (Jiang & Ling, ). In an evolutionary perspective, smoking and alcohol cluster together because they clearly pose a threat to physical health and as risky behaviours help males accomplish short‐term mating (Vincke, ). This is supported by research in undergraduate college students, in which smoking allowed males to project a cool, fun, out‐going and risk‐taking profile to females (Nichter, Nichter, Carkoglu, & Lloyd‐Richardson, ).…”
Section: Introductionmentioning
confidence: 99%